'Rape myths' and a 'reasonable belief' of consent R v Lazarus [2017] NSWCCA 279. Issue 5 (2nd September 2020) - Briggs, Joseph; Scott, Russ
Abstract : Judicial directions in rape trials are designed to emphasise to jury members the importance of negating consent or that the accused believed on reasonable grounds that the complainant consented. After a jury convicted the accused in R v Lazarus [2015], the NSW Court of Appeal in R v Lazarus [2016] NSWCCA 52 found that the trial judge misdirected the jury on the question of the state of mind of the accused at the time of the alleged rape. After a judge sitting without a jury acquitted the accused, the NSW Court of Appeal in R v Lazarus [2017] NSWCCA 279 found that the judge in the re-trial failed to direct herself in relation to making a finding about the steps taken by the accused to establish whether the complainant was consenting. As well as reviewing the reasoning in the decisions, this article discusses rape myths and the justice gap and considers law reform on the issue of consent in rape cases.